A study to assess the knowledge and attitude of staff nurses regarding human rights of mentally ill patients at selected hospitals of Bangalore, India - Thapa, Kriti; Samson, Vimala W. (Journal of Kathmandu Medical College, 2017)
Background: Mental illness raises many human rights issues. People with mental disorders are exposed to a wide range of human rights violation both within and outside the health care context. People with mental illness and their families do not exercise their rights, because of lack of awareness that they have such rights, lack of knowledge about how to effectively assert their rights, and lack of confidence in asserting their rights. The most important factor in ensuring patient’s rights is the knowledge, attitude and commitment of the mental health professionals. Objectives: The objectives of the study were to assess knowledge and attitude of staff nurses regarding human rights of mentally ill patients. Methods: A descriptive approach was adopted for the study. A total of 50 staff nurses working in psychiatric wards of general hospitals and in psychiatric hospitals of Bangalore were selected through purposive sampling technique. A structured knowledge questionnaire was used to assess level of knowledge and a four-point Likert scale was used to assess attitude of nurses regarding human rights of mentally ill patients. Results: The overall mean knowledge score was 50 percent and the overall mean attitude score was 68.65 percent among the staff nurses. Conclusion: The results of the study exposed the requirement of continuing education of staff nurses regarding human rights of mentally ill patients. Journal of Kathmandu Medical College Vol. 6, No. 1, 2017, page: 27-31